Fabrication and characterization of (CaxSr1-x)Si2 films prepared by co-sputtering method. (2020) - Aoyama, Kodai; Shimizu, Takao; Kuramochi, Hideto; Mesuda, Masami; Akiike, Ryo; Ide, Keisuke; Katase, Takayoshi; Kamiya, Toshio; Kimura, Yoshisato; Funakubo, Hiroshi
Abstract: The {100}-oriented (Cax Sr1-x )Si2 thin films have been prepared by co-sputtering method at various deposition temperatures. Constituent phase of the films primarily depends on the deposition temperature and the composition x. Although CaSi2 films consisted of layered structure regardless of deposition temperature, the phase was changed by the deposition temperature: the majority phases of the film deposited at 600°C, 650°C and 700°C were 1T layered structure, 1T layered structure + 2H layered structure and 1T layered structure + 6R layered structure, respectively. When the (Cax Sr1-x )Si2 films deposited at 700°C, the α-SrSi2 -type phase was mainly confirmed below x = 0.17, which is the most stable phase of SrSi2 . However, the main phase of all Cax Sr1-x Si2 films deposited at 600°C changed to be 1T-type layered structure. Substitution with Ca below x = 0.50 in the film deposited at 600°C led to the decrease in the electrical resistivity compared with that of pure SrSi2 .